IDENTIFIKASI VESIKULAR ARBUSKULAR MIKORIZA (VAM) MELALUI METODE KARAKTERISASI MORFOLOGI PADA TANAH PASCA TAMBANG - Aswiani, Nur; Syahri, Yolanda Fitria; Mpia, La (AGRORADIX : Jurnal Ilmu Pertanian, 2024)
This research is a study of FM and FR calculations on post-mining land as well as the identification of Vesicular Arbuscular Mycorrhiza (VAM). on post-nickel mining land. In this research, the method used was a descriptive method. The results obtained were analyzed using descriptive statistics, namely presenting the Vesicular Arbuscular Mycorrhiza (VAM) genera. Calculations were also carried out using statistical formulas which included absolute frequency which shows the presence of a species in a sample and relative frequency which shows the presence of a species in a population (number of spores per 100g of soil). Based on the results of this research and discussion, conclusions can be drawn: 1) The results of identification of the diversity of VAM spore types in post-nickel mining soil found 3 mycorrhizal genera, namely Glomus sp, Acaulospora sp and Gigaspora sp. 2) The results of calculating the largest Absolute Frequency (FM) value are 87.5% and the lowest Absolute Frequency value is 12.5%, while the results of calculating the largest Relative Frequency (FR) value are 8.72% and the lowest relative frequency value is 0.67%.